ANALISIS GERAKAN PEDULI DAN BERBUDAYA LINGKUNGAN HIDUP DI SEKOLAH (PBLHS) DALAM RANGKA AKSI INDONESIA BEBAS SAMPAH PLASTIK 2025 - Suhaila, Suhaila; Novaria, Eva; Syukri, Farhat; Nata, Nasir; Yusuf, Achmad; Nursiwan, Nursiwan (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
The increasing concern about changes in global environmental conditions places environmental issues as a crucial topic. Schools, as the basis for forming the next generation, have a strategic role in fostering environmental awareness through the Environmental Care and Culture Movement in Schools (PBLHS). This study aims to determine teachers' perceptions of the implementation of PBLHS and analyze how the movement's policies are implemented in schools in South Sumatra Province. Using the snowball sampling technique, data were collected from 154 teacher respondents through an online questionnaire and analyzed using descriptive statistics. The findings show teachers' positive attitudes towards PBLHS and the provision of fairly good supporting facilities by most schools, although canteen management related to the provision of environmentally friendly food packaging still needs to be improved. Various PBLHS activities have been carried out, but student involvement and creativity in this movement have not been optimal. The implementation of the PBLHS policy has been proven to have a significant influence on changes in student behavior, especially in reducing plastic use, with teachers acting as facilitators and motivators. Analysis of the dimensions of policy implementation indicates effective communication, efficient resource management, a conducive school environment, and consistent application of policy content and context. This study underlines the success of PBLHS as well as the room for increasing creativity and student participation. ABSTRAKMeningkatnya kekhawatiran terhadap perubahan kondisi alam global menempatkan isu lingkungan hidup sebagai topik krusial. Sekolah, sebagai basis pembentukan generasi penerus, memiliki peran strategis dalam menumbuhkan kepedulian lingkungan melalui Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah (PBLHS). Penelitian ini bertujuan untuk mengetahui persepsi guru terhadap implementasi PBLHS dan menganalisis bagaimana kebijakan gerakan tersebut diterapkan di sekolah-sekolah Provinsi Sumatera Selatan. Menggunakan teknik snowball sampling, data dikumpulkan dari 154 responden guru melalui kuesioner daring dan dianalisis secara statistik deskriptif. Temuan menunjukkan sikap positif guru terhadap PBLHS dan adanya penyediaan fasilitas penunjang yang cukup baik oleh sebagian besar sekolah, meskipun pengelolaan kantin terkait penyediaan pembungkus makanan ramah lingkungan masih perlu ditingkatkan. Berbagai kegiatan PBLHS telah dilaksanakan, namun keterlibatan dan kreativitas siswa dalam gerakan ini belum optimal. Implementasi kebijakan PBLHS terbukti memberikan pengaruh signifikan terhadap perubahan perilaku siswa, khususnya dalam pengurangan penggunaan plastik, dengan guru berperan sebagai fasilitator dan motivator. Analisis dimensi implementasi kebijakan mengindikasikan adanya komunikasi yang efektif, pengelolaan sumber daya yang efisien, lingkungan sekolah yang kondusif, serta penerapan konten dan konteks kebijakan yang konsisten. Penelitian ini menggarisbawahi keberhasilan PBLHS sekaligus ruang peningkatan untuk kreativitas dan partisipasi siswa.